Magnetic targeting of microbubbles against physiologically relevant flow conditions - Owen, J; Rademeyer, P; Chung, D; Cheng, Q; Holroyd, D; Coussios, C; Friend, P; Pankhurst, QA; Stride, E (Royal Society, 2015)
The localization of microbubbles to a treatment site has been shown to be essential to their effectiveness in therapeutic applications such as targeted drug delivery and gene therapy. A variety of different strategies for achieving localization has been investigated, including biochemical targeting, acoustic radiation force, and the incorporation of superparamagnetic nanoparticles into microbubbles to enable their manipulation using an externally applied magnetic field. The third of these strategies has the advantage of concentrating microbubbles in a target region without exposing them to ultrasound, and can be used in conjunction with biochemical targeting to achieve greater specificity. Magnetic microbubbles have been shown to be effective for therapeutic delivery in vitro and in vivo. Whether this technique can be successfully applied in humans however remains an open question. The aim of this study was to determine the range of flow conditions under which targeting could be achieved. In vitro results indicate that magnetic microbubbles can be retained using clinically acceptable magnetic fields, for both the high shear rates (approx. 10(4) s(-1)) found in human arterioles and capillaries, and the high flow rates (approx. 3.5 ml s(-1)) of human arteries. The potential for human in vivo microbubble retention was further demonstrated using a perfused porcine liver model.